Financial accounting - Meigs, Robert F.; Meigs, Robert F. (Boston, Mass. : Irwin/McGraw-Hill, 1998)
An introductory text in financial accounting. This volume shows how to prepare and use financial accounting information. In this edition, accounting research and analysis has been increased to provide a greater user-orientation, while coverage of procedures has been reduced.
Rev. ed. of: Financial accounting / Robert F. Meigs, Walter B. Meigs, Mary A. Meigs. 8th ed. c1995.
Includes bibliographical references and index.
oif 11/03/15
Loan
Keywords: Accounting